Riba free economy as the enabler of halal eco-system / Zulkarnain Yusoff ...[et al.] - Yusoff, Zulkarnain; Ismail@Ahmad, Muslim; Othman, Roslina; Ismail, Mohd Nasir; Ismail, Mohd Saufi (2019)
This research applies bibliometric tool in analyzing riba free or halal economy in research available in online databases. Dataset are citations from Scopus, ProQuest and ScienceDirect. Triple element mapping review is used to establish concept definition. Conceptual definition surrounding riba, usury and interest are highlighted and debated in literature. The aim of this research is to analyze subject relation of halal economy as the enabler of halal eco-system. VOSviewer, GEPHI, JabRef and Microsoft® Excel is used as tool of bibliometric visualization and data statistical analysis. Datasets are citations from Scopus, ProQuest and ScienceDirect databases. From Scopus database, 130 journal articles were obtained ranging from 1982 to 2018, from ProQuest 646 citations ranging from 1989 to 2018 and from ScienceDirect 313 citations of 26 years (1993-2019). Total citation datasets 1,089 with a time span of 27 years. Analysis result are divided into clusters of co-occurrence of index term in titles and abstracts. Authors with the highest citation link is also highlighted and highest output journal is also outlined.